Comparison of HTP catalyst performance for different internal monolith structures. (November 2019) - Koopmans, Robert-Jan; Nandyala, Varun Reddy; Pavesi, Sara; Batonneau, Yann; Beauchet, Romain; Maleix, Corentin; Schwentenwein, Martin; Spitzbart, Manfred; Altun, Altan Alpay; Scharlemann, Carsten
Abstract: A new technology for the manufacturing of 3D-printed ceramic catalyst support structures enables further optimisation of the catalyst, including the size and the internal geometry. An important design consideration for catalysts used in monopropellant thrusters is the size for a given design thrust level. A too small size may lead to only a partly decomposition of the incoming propellant. A too large size may lead to unnecessary heat loss to the environment and an excessive pressure drop. Both cases will result in a reduced performance. In the current investigation, four catalyst designs were subjected to a range of mass flow rates, thereby varying the average residence time in the chamber. It was found that shorter residence times lead to higher average chamber temperatures. This suggests that the catalyst is too large. Although the results for each internal design cannot be compared directly to each other, the convex tetrahedron design seems to be slightly better. Highlights: Catalyst support structures can be printed in different geometries. Residence time insensitive to Re number and void fraction. Maximum temperature design dependent, but insensitive to Re number and void fraction.